2014
DOI: 10.1590/s0100-83582014000400007
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre métodos para determinar o período anterior à interferência de plantas daninhas em feijoeiros com distintos tipos de hábitos de crescimento

Abstract: RESUMO -A interferência causada pelas plantas daninhas pode reduzir em até 80% a produtividade de grãos do feijão quando não manejadas de forma correta. Portanto, a decisão sobre o momento de controlá-las é um dos principais aspectos do manejo integrado. Nesse sentido, objetivou-se com este trabalho determinar o período anterior à interferência das plantas daninhas (PAI) em cultivares de feijão com diferentes tipos de hábitos de crescimento. Adotou-se o delineamento experimental de blocos casualizados com quat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 14 publications
2
15
0
2
Order By: Relevance
“…Although, when the bean plant was analyzed in relation to the biggest LA (100 x 10³ cm 2 m -2 ), it was determined that the cultivars with the biggest and smallest losses was, respectively, IPR Uirapuru -34.13% and BRS Campeiro -14.28% (Figure 2). It can be inferred that the cultivars competition degree, in relation to the beggartick, is influenced by the leaf area of the weed, according to what was determined by Parreira et al (2014), when evaluating the competition between bean cultivars (type carioca) and weeds.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although, when the bean plant was analyzed in relation to the biggest LA (100 x 10³ cm 2 m -2 ), it was determined that the cultivars with the biggest and smallest losses was, respectively, IPR Uirapuru -34.13% and BRS Campeiro -14.28% (Figure 2). It can be inferred that the cultivars competition degree, in relation to the beggartick, is influenced by the leaf area of the weed, according to what was determined by Parreira et al (2014), when evaluating the competition between bean cultivars (type carioca) and weeds.…”
Section: Resultsmentioning
confidence: 99%
“…It was determined, on the whole, for most of the evaluated variables, that the estimated values for the i parameter tend to be smaller in the BRS Esplendor, IPR Tuiuiú and Fepagro 26 cultivars, while the smaller competitiveness was verified to the IPR Uirapuru cultivars, for the variable PP, and BRS Supremo cultivars, for GC and DM, which presented the biggest losses in grain productivity when compared to the others (Figures 1, 2, 3 and 4). Many researches have reported the existence of differentiation among cultivars in their competitive ability in crops when in presence of weeds, fact that is attributed to the group of morphophysiological characteristics inherent to them (Barroso et al, 2010;Vidal et al, 2010;Kalsing and Vidal, 2013;Parreira et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The turnip was the predominant species, with 1.700 g m -2 of dry matter, followed by extinguishes fire with 900 g m Parreira et al (2013Parreira et al ( , 2014 and found that, in R. raphanistrum reached extremely high density and dry weight values drastically reducing crop yields that were present. When analyzing productivity when the weed community was present throughout the crop cycle, there were drastic losses in production reducing 84.89%.…”
Section: Revmentioning
confidence: 95%